Is crying a self-soothing behavior? - Gračanin, Asmir; Bylsma, Lauren M.; Vingerhoets, Ad J. J. M. (Frontiers in Psychology, 2014)
This contribution describes the current state-of-the-art of the scientific literature regarding the self-soothing effects of crying. Starting from the general hypothesis that crying is a self-soothing behavior, we consider different mechanisms through which these effects may appear. In the first section we briefly explain the main functions of human crying. Then we define self-soothing in terms of homeostatic processes of mood regulation and stress reduction and we underline the importance of distinguishing self-soothing effects of crying from social-soothing that it may elicit. We then provide a comprehensive review of the putative mood enhancing and relieving effects of crying and their variations stemming from characteristics of crying person, antecedents, manifestations, and social consequences of crying. We also discuss the possible methodological explanations for the seemingly discrepant findings regarding mood improvement and relief that may follow crying. We then provide theoretical and empirical support for our general hypothesis that crying is a self-soothing behavior by presenting and evaluating the possible physiological, cognitive, and behavioral mechanisms that may play a mediating role in the relationship between crying and homeostatic regulation that includes mood improvement and relief. Starting from the idea that social-soothing and self-soothing mechanisms share the same physiological systems, we propose that biological processes act in parallel with learning and reappraisal processes that accompany crying, which results in homeostatic regulation. Given the parallels between self-soothing behaviors in humans and animals, we also propose that crying might self-soothe through a mechanism that shares key properties with rhythmical, stereotypic behaviors. We conclude that, in addition to the importance of socially mediated mechanisms for the mood enhancing effects of crying, there is converging evidence for the direct, self-soothing effects of crying.